Flow-Induced Vibrations of Five Cylinders in Uniform Current - Henry Francis Annapeh; Victoria Kurushina; Guilherme Rosa Franzini (Vibration)
Predicting flow-induced vibration (FIV) of multiple slender structures remains a modern challenge in science and engineering due to the phenomenon’s sensitivity to layout parameters and the emergence of oscillations driven by multiple mechanisms. The present study examines the FIV of five circular cylinders with two degrees of freedom arranged in a ‘cross’ configuration and subjected to a uniform current. A computational fluid dynamics approach, solving the transient, incompressible 2D Navier–Stokes equations, is employed to analyze the influence of the spacing ratio and reduced velocity <semantics>Ur</semantics> on the vibration response and wake dynamics. The investigation includes model verification and parametric studies for several spacing ratios. Results reveal vortex-induced vibrations (VIVs) in some of the cylinders in the arrangement and combined vortex-induced and wake-induced vibration (WIV) in others. Lock-in is observed at <semantics>Ur</semantics> = 7 for the upstream cylinder, while the midstream and downstream cylinders exhibit the highest vibration amplitudes due to wake interference. Larger spacing ratios amplify the oscillations of the downstream cylinders, while the side-by-side cylinders display distinct frequency responses. Motion trajectories transition from figure-of-eight patterns to enclosed loops as <semantics>Ur</semantics> increases, with specifically complex oscillations emerging at higher velocities. These findings provide insights into multi-body VIV, relevant to offshore structures, marine risers, and heat exchangers.